Optimalisasi Penanganan Pasca Panen Kakao Melalui Peningkatan Kapasitas Petani di Kabupaten Soppeng - Tjanring, Junaedi; Syahruni Thamrin; Andi Besse Poleuleng (JPM: Jurnal Pengabdian Masyarakat, 2025)
The Sekkang Mata II Farmers Group is one of the farming groups located in Tettikenrarae Village, Marioriwawo District, which has the potential to produce cocoa for the export market. However, there are currently obstacles in meeting the demand for high-quality and sustainable cocoa beans due to a lack of adequate skills and equipment. The purpose of this community service implementation focuses on improving production, particularly through the application of post-harvest technology, by enhancing the knowledge and skills of partners in meeting export market demands. The method of implementing community service activities is directed towards solving the partner's priority problems through activities (1) counseling/training, (2) assistance, and (3) technical guidance. The results of the community service implementation obtained after the counseling show that partner farmers have understood the importance of added value to cocoa bean products needed for meeting the export market, which can be produced from healthy cocoa beans. Understanding related to this matter is demonstrated by partner farmers through efforts in fruit care in cocoa plantations, sorting beans during harvest, and preparing cocoa bean fermentation activities, including providing fermentation boxes and post-fermentation bean drying facilities. At the same time, partner farmers have also been striving to establish sales cooperation for fermented cocoa with exporting companies in Makassar. This collaboration is not only to ensure the continuity of marketing for fermented cocoa from partner farmers but also to meet the global market needs of exporting companies.